Carnosol controls the human glioblastoma stemness features through the epithelial-mesenchymal transition modulation and the induction of cancer stem cell apoptosis. Issue 1 (December 2017) - Giacomelli, Chiara; Daniele, Simona; Natali, Letizia; Iofrida, Caterina; Flamini, Guido; Braca, Alessandra; Trincavelli, M.; Martini, Claudia
Abstract A high cell proliferation rate, invasiveness and resistance to chemotherapy are the main features of glioblastoma (GBM). GBM aggressiveness has been widely associated both with a minor population of cells presenting stem-like properties (cancer stem-like cells, CSCs) and with the ability of tumor cells to acquire a mesenchymal phenotype (epithelial-mesenchymal transition, EMT). Carnosol (CAR), a natural inhibitor of MDM2/p53 complex, has been attracted attention for its anti-cancer effects on several tumor types, including GBM. Herein, the effects of CAR on U87MG-derived CSC viability and stemness features were evaluated. CAR decreased the rate of CSC formation and promoted the CSC apoptotic cell death through p53 functional reactivation. Moreover, CAR was able to control the TNF-α/TGF-β-induced EMT, counteracting the effects of the cytokine on EMT master regulator genes (Slug, Snail, Twist and ZEB1) and modulating the activation of miR-200c, a key player in the EMT process. Finally, CAR was able to increase the temozolomide (TMZ) anti-proliferative effects. These findings demonstrate that CAR affected the different intracellular mechanism of the complex machinery that regulates GBM stemness. For the first time, the diterpene was highlighted as a promising lead for the development of agents able to decrease the stemness features, thus controlling GBM aggressiveness.